2004
DOI: 10.1159/000082042
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E-Coated Dialyzer Membranes Downregulate Expression of Monocyte Adhesion and Co-Stimulatory Molecules

Abstract: Background: In patients on chronic hemodialysis leukocyte activation has been related to the impaired function of the immune system. In this study we investigated if the vitamin E-coated dialyzer membrane could reduce monocyte activation thereby improving cellular immunity. Methods: This hypothesis was tested in a prospective crossover trial in which 14 stable hemodialysis patients were switched from the baseline hemophane dialyzer to a vitamin E-coated and thereafter a polysulphone dialyzer membrane or vice v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(29 reference statements)
2
7
0
Order By: Relevance
“…Our results show that ex-vivo GT treatment of sputum-derived airway macrophages caused decreases in certain phagocytic indices, down-regulated expression of specific cell surface proteins and that atopic status appears to be an important factor. These findings suggest that GT modulates macrophage activation and is consistent with findings in the earlier studies [28, 34, 36, 37]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results show that ex-vivo GT treatment of sputum-derived airway macrophages caused decreases in certain phagocytic indices, down-regulated expression of specific cell surface proteins and that atopic status appears to be an important factor. These findings suggest that GT modulates macrophage activation and is consistent with findings in the earlier studies [28, 34, 36, 37]. …”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, Betjes et al [36] reported decreased expression of MHC-I and the co-stimulatory molecules CD86 and CD40 on blood monocytes associated with the use of vitamin E coated dialysis membranes in hemodialysis patients. We did not study the effects of GT on T-cell function or of antigen processing and presentation by sputum antigen presenting cells.…”
Section: Discussionsupporting
confidence: 93%
“…Preliminary clinical studies observed that these heparin-bonded dialyzers permitted heparin-free dialysis, 31 although later studies reported a reduction in heparin requirements. 33 Initially, vitamin E was bonded to modified cellulosic membranes, and only recently has vitamin E been successfully bonded to polysulfone membranes, and as yet, there has been no convincing study that suggests a clinical benefit for hemodialysis patients. 33 Initially, vitamin E was bonded to modified cellulosic membranes, and only recently has vitamin E been successfully bonded to polysulfone membranes, and as yet, there has been no convincing study that suggests a clinical benefit for hemodialysis patients.…”
Section: Alteration Of Membrane Surface Propertiesmentioning
confidence: 99%
“…Other reports demonstrated the positive effects related to (a) decreased oxidative stress [72,73,74,75,76,77,78,79,80,81]; (b) suppression of leukocyte activation [82,83,84,85,86,87,88]; (c) reduction of anticoagulant dosage [89]; (d) improved biocompatibility [90], and (e) decreased levels of advanced glycation end products [91]. Moreover, a recent study by Kirmizis et al [92] showed lowered levels of the inflammatory markers CRP, IL-6, and soluble intercellular adhesion molecule-1 in 35 patients when treated with Excebrane with respect to baseline treatments carried out with conventional low- or medium-flux dialyzers, while no change was observed in a matched control group of 25 patients who underwent treatment with these later unmodified dialyzers for the whole observation time.…”
Section: Vitamin E-bonded Dialyzersmentioning
confidence: 99%